Role-plays versus natural data: asking for a drink at a cafeteria in Peninsular Spanish - Bataller Fuster, Rebeca (Íkala, Revista de Lenguaje y Cultura, 2013)
The purpose of this study is to compare the data collected, via two methods, from two groups of Peninsular Spanish native speakers in a service encounter scenario. The methods chosen are open role-plays and naturally occurring interactions, two frequently used approaches in the field of pragmatics. The naturalistic data from this study consisted of request-for-service transactions at cafeterias in Valencia, Spain; these were recorded with audio equipment and then analyzed at the illocutionary and discourse levels. The features analyzed were the strategies and mitigating devices used in all phases of the interactions. The structure and length of interactions from each dataset were also compared. The results of this comparative study indicate that the role-play data resembled the naturalistic interactions in some respects, but there were also some significant differences between the two datasets that may be attributed to the particular type of collection method. <!–EndFragment–>